2002
DOI: 10.1038/sj.bmt.1703331
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of Epstein–Barr virus load in 85 hematopoietic stem cell transplants

Abstract: Summary:EBV viral load (EBV-VL) in PBMC was prospectively determined by semi-quantitative PCR in 85 stem cell transplants (40 genoidentical, 45 non-genoidentical) in order to characterize the kinetics of EBV-VL and to assess the ability of this measure to predict the development of EBV-induced lymphoproliferative disease (EBV-LPD). PCR was performed prior to and after transplantation. An EBV-VL Ͼ300 copies/ g DNA was chosen as the threshold for risk of developing an EBV-LPD. Two hundred and fifty-eight EBV-VL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 47 publications
0
35
2
Order By: Relevance
“…For protection they were given immunoglobulins after transplantation resulting in high IgG antibody titers against virus capsid antigen and nuclear antigen of EBV. [Kenagy et al, 1995;Martinez et al, 1995;Bai et al, 1997;Rowe et al, 1997;Brengel-Pesce et al, 2002;Gärtner et al, 2002;Sirvent-von Bueltzingsloewen et al, 2002]. High amounts of EBV in peripheral blood mononuclear cells were detected in these patients [Savoie et al, 1994;Rooney et al, 1995;Lucas et al, 1998].…”
Section: Ebv Serostatusmentioning
confidence: 99%
See 1 more Smart Citation
“…For protection they were given immunoglobulins after transplantation resulting in high IgG antibody titers against virus capsid antigen and nuclear antigen of EBV. [Kenagy et al, 1995;Martinez et al, 1995;Bai et al, 1997;Rowe et al, 1997;Brengel-Pesce et al, 2002;Gärtner et al, 2002;Sirvent-von Bueltzingsloewen et al, 2002]. High amounts of EBV in peripheral blood mononuclear cells were detected in these patients [Savoie et al, 1994;Rooney et al, 1995;Lucas et al, 1998].…”
Section: Ebv Serostatusmentioning
confidence: 99%
“…between 200 copies/10 5 peripheral blood mononuclear cells , ≥300/10 5 peripheral blood mononuclear cells [Cesaro et al, 2004], >300/µg DNA [Sirvent-von Bueltzingsloewen et al, 2002], >10 2,5 /µg DNA [Hoshino et al, 2001], >500/75,000 peripheral blood mononuclear cells [Frias et al, 2001], >1,000/10 5 cells [Bacigalupo, 2005], >4,000/µg DNA [Wagner et al, 2004], 6,215/ml blood [Yancoski et al, 2004] and 10,000/µg DNA [Orentas et al, 2003]. As shown in Table 2, EBV load of >100,000 EBV-genome copies /10 5 peripheral blood mononuclear cells significantly predicts EBV lymphoproliferative disease in our study, whereas patients with ≤1,000 EBV-genome copies/10 5 peripheral blood mononuclear cells did not develop a lymphoproliferative disorder.…”
Section: Cut-offmentioning
confidence: 99%
“…daclizumab, pentostatin) have not been evaluated in large studies. Sirvent-von Bueltzingsloewen et al 28 reported that a rapid increase in viral burden was a better predictor of disease onset than simply exceeding an absolute PCR threshold. Other groups have not clearly corroborated this experience, 9,24 but the rate of rise has not been adequately evaluated as a potential harbinger of PTLD.…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 99%
“…Furthermore, these values overlap significantly with PCR values from patients who did not develop PTLD. 9,12,28,32 Finally, the threshold PCR values used to define patients at risk for PTLD were established by retrospectively analyzing single-institution experiences and have, for Table 1 A comparison of published studies using polymerase chain reaction (PCR) for measuring Epstein-Barr viral load in the peripheral blood of HSCT recipients, either prior to the clinical presentation of PTLD (above) or at the time of presentation (below)…”
Section: Potential Shortcomings Of the Preemptive Pcr Approachmentioning
confidence: 99%
See 1 more Smart Citation